MATHEMATICS LITERACY MOVEMENT FOR STUDENTS TO INCREASE CREATIVE THINKING ABILITY AT SDN KENARI 07 PAGI - Alberth Manurung; Abdul Halim; Ainur Rasyid (KARYA ABDI, 2021)
Mathematics is the science of logic regarding forms, structures, quantities and concepts related to one another. In the concept it is always related to everyday human life. Learning Mathematics in the form of the Student Literacy Movement is not only an increase in curiosity but always the development of creative thinking skills, Mathematics is the science of calculating which aims to instill and develop a counting process in teachers. Based on the results of observations at SDN Kenari 07 Pagi on the teacher learning process still using conventional or teacher-centered teaching methods as information providers, with the student literacy movement it is expected to improve the good quality of each problem-solving concept in the form of question applications. Keywords: Literacy Movement, Creative Thinking Ability, Mathematics